Experimental evidence for protein oxidative damage and altered antioxidant defense in patients with medium‐chain acyl‐CoA dehydrogenase deficiency. Issue 5 (13th March 2014) - Derks, Terry G. J.; Touw, Catharina M. L.; Ribas, Graziela S.; Biancini, Giovana B.; Vanzin, Camila S.; Negretto, Giovanna; Mescka, Caroline P.; Reijngoud, Dirk Jan; Smit, G. Peter A.; Wajner, Moacir; Vargas, Carmen R.
Abstract: The objective of this study was to test whether macromolecule oxidative damage and altered enzymatic antioxidative defenses occur in patients with medium‐chain acyl coenzyme A dehydrogenase (MCAD) deficiency. We performed a cross‐sectional observational study of in vivo parameters of lipid and protein oxidative damage and antioxidant defenses in asymptomatic, nonstressed, MCAD‐deficient patients and healthy controls. Patients were subdivided into three groups based on therapy: patients without prescribed supplementation, patients with carnitine supplementation, and patients with carnitine plus riboflavin supplementation. Compared with healthy controls, nonsupplemented MCAD‐deficient patients and patients receiving carnitine supplementation displayed decreased plasma sulfhydryl content (indicating protein oxidative damage). Increased erythrocyte superoxide dismutase (SOD) activity in patients receiving carnitine supplementation probably reflects a compensatory mechanism for scavenging reactive species formation. The combination of carnitine plus riboflavin was not associated with oxidative damage. These are the first indications that MCAD‐deficient patients experience protein oxidative damage and that combined supplementation of carnitine and riboflavin may prevent these biochemical alterations. Results suggest involvement of free radicals in the pathophysiology of MCAD deficiency. The underlying mechanisms behind the increased SOD activity upon carnitine supplementation need to be determined. Further studies are necessary to determine the clinical relevance of oxidative stress, including the possibility of antioxidant therapy.